2020
DOI: 10.1016/s0140-6736(20)31927-9
|View full text |Cite|
|
Sign up to set email alerts
|

Lancet COVID-19 Commission Statement on the occasion of the 75th session of the UN General Assembly

Abstract: The Lancet COVID-19 Commission was launched on July 9, 2020, to assist governments, civil society, and UN institutions in responding effectively to the COVID-19 pandemic. The Commission aims to offer practical solutions to the four main global challenges posed by the pandemic: suppressing the pandemic by means of pharmaceutical and non-pharmaceutical interventions; overcoming humanitarian emergencies, including poverty, hunger, and mental distress, caused by the pandemic; restructuring public and private finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 53 publications
0
104
0
7
Order By: Relevance
“…Little is, however, known regarding macrolevel association of NCD risk factors and diseases on COVID-19 burden and mortality. A significant association of aging with adverse outcomes in COVID-19 has been reported in China, Europe and USA [ 1 ]. In India a study reported heightened adverse events among the elderly using a modeling algorithm [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Little is, however, known regarding macrolevel association of NCD risk factors and diseases on COVID-19 burden and mortality. A significant association of aging with adverse outcomes in COVID-19 has been reported in China, Europe and USA [ 1 ]. In India a study reported heightened adverse events among the elderly using a modeling algorithm [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, association of COVID-19 with sociodemographic factors such as urbanization and other indices of development and better healthcare access and quality indices could indicate better diagnosis of the condition in these locations [ 1 ]. In lesser developed states of the country as well as rural areas of India it is likely that the condition is not diagnosed due to lack of access to quality healthcare [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Argentina is close to the lower limit, with only 2.4 tests/cc, which corresponds to a positivity in the order of 40%. [1].…”
Section: Introductionmentioning
confidence: 99%